  MathScore EduFighter is one of the best math games on the Internet today. You can start playing for free!

## System of Equations Substitution - Sample Math Practice Problems

The math problems below can be generated by MathScore.com, a math practice program for schools and individual families. References to complexity and mode refer to the overall difficulty of the problems as they appear in the main program. In the main program, all problems are automatically graded and the difficulty adapts dynamically based on performance. Answers to these sample questions appear at the bottom of the page. This page does not grade your responses.

See some of our other supported math practice problems.

### Complexity=3

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

 1 -x + y = - 1 x + 3y = - 11 First equation solved for y: Answer (x,y): 2 x + 3y = 3 3x - 2y = - 2 First equation solved for y: Answer (x,y):

### Complexity=5

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

 1 -x - 2y = - 5 2x - 3y = - 18 First equation solved for y: Answer (x,y): 2 4x + y = 1 x + y = - 2 First equation solved for y: Answer (x,y):

### Complexity=10

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

 1 - 8x - y = 32 3x + y = - 17 First equation solved for y: Answer (x,y): 2 - 9x - 10y = 64 x - y = - 5 First equation solved for y: Answer (x,y):

### Complexity=13

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

 1 x + 2y = 20 -x + 12y = 134 First equation solved for y: Answer (x,y): 2 9x - 8y = 72 3x + 10y = - 90 First equation solved for y: Answer (x,y):

### Complexity=14

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

 1 x + 2y = - 5 - 10x - 13y = - 13 First equation solved for y: Answer (x,y): 2 3x + 4y = - 57 10x + 7y = - 152 First equation solved for y: Answer (x,y):

### Complexity=15

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

 1 - 14x - 9y = 41 5x + 7y = - 26 First equation solved for y: Answer (x,y): 2 3x + 4y = 18 x - 13y = - 166 First equation solved for y: Answer (x,y):

### Complexity=3

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

1-x + y = - 1
x + 3y = - 11
First equation solved for y:

Solution
Solve the first equation for y
-x + y + x = - 1 + x
y = x - 1

Original Equations
-x + y = - 1
x + 3y = - 11

Solving for y in the first equation yields:
y = x - 1

Substitute this into the second equation:
x + 3(x - 1) = - 11
4x - 3 = - 11
Now solving for x...
4x - 3 + 3 = - 11 + 3
4x = - 8

Divide by 4

x = - 2

Now plug value of x into the original first equation
- 1 • - 2 + y = - 1
2 + y = - 1
2 + y - 2 = - 1 - 2
y = - 3

2x + 3y = 3
3x - 2y = - 2
First equation solved for y:

Solution
Solve the first equation for y
x + 3y - x = 3 - x
3y = -x + 3

Divide by 3

Original Equations
x + 3y = 3
3x - 2y = - 2

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 3

11x = 0

Divide by 11

x = 0

Now plug value of x into the original first equation
0 + 3y = 3
3y = 3
Divide by 3

y = 1

### Complexity=5

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

1-x - 2y = - 5
2x - 3y = - 18
First equation solved for y:

Solution
Solve the first equation for y
-x - 2y + x = - 5 + x
- 2y = x - 5

Divide by - 2

Original Equations
-x - 2y = - 5
2x - 3y = - 18

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 2

7x = - 21

Divide by 7

x = - 3

Now plug value of x into the original first equation
- 1 • - 3 - 2y = - 5
3 - 2y = - 5
3 - 2y - 3 = - 5 - 3
- 2y = - 8

Divide by - 2

y = 4

24x + y = 1
x + y = - 2
First equation solved for y:

Solution
Solve the first equation for y
4x + y - 4x = 1 - 4x
y = - 4x + 1

Original Equations
4x + y = 1
x + y = - 2

Solving for y in the first equation yields:
y = - 4x + 1

Substitute this into the second equation:
x + - 4x + 1 = - 2
- 3x + 1 = - 2
Now solving for x...
- 3x + 1 - 1 = - 2 - 1
- 3x = - 3

Divide by - 3

x = 1

Now plug value of x into the original first equation
4 • 1 + y = 1
4 + y = 1
4 + y - 4 = 1 - 4
y = - 3

### Complexity=10

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

1- 8x - y = 32
3x + y = - 17
First equation solved for y:

Solution
Solve the first equation for y
- 8x - y + 8x = 32 + 8x
-y = 8x + 32

Multiply by - 1
 -y(- 1) = (8x + 32)(- 1)

y = - 8x + - 32

y = - 8x - 32

Original Equations
- 8x - y = 32
3x + y = - 17

Solving for y in the first equation yields:
y = - 8x - 32

Substitute this into the second equation:
3x + - 8x - 32 = - 17
- 5x - 32 = - 17
Now solving for x...
- 5x - 32 + 32 = - 17 + 32
- 5x = 15

Divide by - 5

x = - 3

Now plug value of x into the original first equation
- 8 • - 3 - y = 32
24 - y = 32
24 - y - 24 = 32 - 24
-y = 8

Multiply by - 1
 -y(- 1) = 8 • - 1

y = - 8

2- 9x - 10y = 64
x - y = - 5
First equation solved for y:

Solution
Solve the first equation for y
- 9x - 10y + 9x = 64 + 9x
- 10y = 9x + 64

Divide by - 10

Original Equations
- 9x - 10y = 64
x - y = - 5

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 10

19x = - 114

Divide by 19

x = - 6

Now plug value of x into the original first equation
- 9 • - 6 - 10y = 64
54 - 10y = 64
54 - 10y - 54 = 64 - 54
- 10y = 10

Divide by - 10

y = - 1

### Complexity=13

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

1x + 2y = 20
-x + 12y = 134
First equation solved for y:

Solution
Solve the first equation for y
x + 2y - x = 20 - x
2y = -x + 20

Divide by 2

Original Equations
x + 2y = 20
-x + 12y = 134

Solving for y in the first equation yields:

Substitute this into the second equation:

- 7x + 120 = 134
Now solving for x...
- 7x + 120 - 120 = 134 - 120
- 7x = 14

Divide by - 7

x = - 2

Now plug value of x into the original first equation
- 2 + 2y = 20
- 2 + 2y = 20
- 2 + 2y + 2 = 20 + 2
2y = 22

Divide by 2

y = 11

29x - 8y = 72
3x + 10y = - 90
First equation solved for y:

Solution
Solve the first equation for y
9x - 8y - 9x = 72 - 9x
- 8y = - 9x + 72

Divide by - 8

Original Equations
9x - 8y = 72
3x + 10y = - 90

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 4

57x = 0

Divide by 57

x = 0

Now plug value of x into the original first equation
9 • 0 - 8y = 72
- 8y = 72
Divide by - 8

y = - 9

### Complexity=14

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

1x + 2y = - 5
- 10x - 13y = - 13
First equation solved for y:

Solution
Solve the first equation for y
x + 2y - x = - 5 - x
2y = -x - 5

Divide by 2

Original Equations
x + 2y = - 5
- 10x - 13y = - 13

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 2

- 7x = - 91

Divide by - 7

x = 13

Now plug value of x into the original first equation
13 + 2y = - 5
13 + 2y = - 5
13 + 2y - 13 = - 5 - 13
2y = - 18

Divide by 2

y = - 9

23x + 4y = - 57
10x + 7y = - 152
First equation solved for y:

Solution
Solve the first equation for y
3x + 4y - 3x = - 57 - 3x
4y = - 3x - 57

Divide by 4

Original Equations
3x + 4y = - 57
10x + 7y = - 152

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 4

19x = - 209

Divide by 19

x = - 11

Now plug value of x into the original first equation
3 • - 11 + 4y = - 57
- 33 + 4y = - 57
- 33 + 4y + 33 = - 57 + 33
4y = - 24

Divide by 4

y = - 6

### Complexity=15

Solve by substitution.
In step 1, answer in the form   y = mx + b,   such as   y = 3x + 2   or   y = -x/3 - 6.
In step 2, answer in the form (x,y). For example: (-2,3).

1- 14x - 9y = 41
5x + 7y = - 26
First equation solved for y:

Solution
Solve the first equation for y
- 14x - 9y + 14x = 41 + 14x
- 9y = 14x + 41

Divide by - 9

Original Equations
- 14x - 9y = 41
5x + 7y = - 26

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 9

- 53x = 53

Divide by - 53

x = - 1

Now plug value of x into the original first equation
- 14 • - 1 - 9y = 41
14 - 9y = 41
14 - 9y - 14 = 41 - 14
- 9y = 27

Divide by - 9

y = - 3

23x + 4y = 18
x - 13y = - 166
First equation solved for y:

Solution
Solve the first equation for y
3x + 4y - 3x = 18 - 3x
4y = - 3x + 18

Divide by 4

Original Equations
3x + 4y = 18
x - 13y = - 166

Solving for y in the first equation yields:

Substitute this into the second equation:

Now solving for x...

Multiply by 4

43x = - 430

Divide by 43

x = - 10

Now plug value of x into the original first equation
3 • - 10 + 4y = 18
- 30 + 4y = 18
- 30 + 4y + 30 = 18 + 30
4y = 48

Divide by 4

y = 12   